Anti-Terrorism Education: Max Weber's Four Rationalities Approach - Ikhwansyah, Muhammad Fuad; Anwar, Khairil (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Terrorism has harmful effects on both individuals and society. This research uses a descriptivequalitative approach, gathering data through a literature review. The findings conclude that terrorism is an act of violence carried out in various ways to intimidate groups or individuals in order to uphold ideologies, beliefs, politics, or similar aims. Terrorism falls into six categories: cyberterrorism, basic terrorism, revolutionary, sub-revolutionary, epiphenomenal, and repressive. According to Max Weber's theory of rationality, the causes of terrorism are: Instrumental rationality: Terrorism as a tool to gain territory or influence. Affective rationality: Terrorist acts as a form of affective expression. Traditional rationality: Terrorism as a customary practice. Value rationality: Terrorist acts as a manifestation of values and ideology. Additionally, there's another rationality related toterrorism: distorted rationality, where terrorism occurs due to a misunderstanding of the meaning of religion itself. Anti-terrorism education can be implemented by addressing the root causes of terrorism, empowering communities, promoting moderation in understanding or religion, instilling compassion, nationalism, and unity, and preventing factors that trigger terrorist acts.